High Altitude Ramsar Sites of Nepal - Upadhaya, Suraj; Chalise, Lina; Paudel, Rajan P (The Initiation, 2010)
Nepal, signing in Ramsar Convention, has shown its willingness and commitment to wetland conservation. Himalayan wetlands are increasingly on limelight due to its vulnerability to Glacier lake outburst (GLOF), one of so called consequences of climate change. This article is a compilation of fact sheets about four high altitude Ramsar sites of Nepal: Gokyo and associated wetlands, Gosaikunda and associated wetlands, Phoksundo Lake and Rara lake. Key Words: Gokyo, Gosaikunda, Phoksundo, Rara, High altitude wetlands DOI: 10.3126/init.v3i0.2505 The Initiation Vol.3 2009 p.135-148